A REVIEW ON RASAYANA WITH RESPECT TO DAY TO DAY CLINICLAL PRACTICE - Christy Jose Cherian (International Journal of Applied Ayurved Research, 2015)
Ayurveda the eternal life science from many centuries proved to be the most efficient tool in the health management system. Statistics says on worldwide basis one among the three deaths is from infectious or communicable diseases. Deaths causing due to communicable diseases covers 55% in developing countries and 14% in developed countries. In Ayurvedic science the communicable diseases are mentioned under the janapadhodwamsa includes the causative agents; its features the methods of prevention of diseases have been clearly explained. The techniques of managing communicable diseases advised include the usage of rasayana therapy and panchakarma procedures. Apart from the treatments targeting the causative organism these treatment modalities aims in bringing back the normal health to the individual and curing the disease. These methods prove efficient in the management of disease as well as maintaining the health and effectively preventing any upadravas or secondary disorders. . An effort has been made to find possible Ayurvedic comparison to the current most prevalent communicable diseases and classify under the pranavaha srotas(respiratory system), annavaha srotas(alimentary canal), udakavaha srotas( channels carrying fluids ), rasavaha and rakthavahasrotas(lymph and circulatory system) based on the particular signs and symptoms and the system involved. Also aims to provide information among the rasayana oushadies which can be in co operated in day to day clinical practice along with vyadhi hara chikitsa. This may provide answer to the challenge of resistant type micro organism and the side effects causing by conventional causative organism targeted treatment.